Knowledge, awareness and use of current practice of palliative care amongst physiotherapists - Abdulsalam M. Yakasai; Sonil S. Maharaj; Umar M. Gidado; Jibril M. Nuhu; Sani A. Haruna; Musa S. Danazumi (South African Journal of Physiotherapy, 2023)
Background: Recently, there has been a marked increase in the incidence of cancer, HIV, and other noncommunicable diseases globally. Thus, the demand for palliative care (PC), including end-of-life care, continues to grow worldwide. Physiotherapy has an important role in PC as it aims to alleviate symptoms and improve quality of life by optimising independent levels of function.